On the Factors Influencing EFL Students’ Intercultural Competence - Sobkowiak, Paweł (Studia Anglica Posnaniensia, 2019)
Cultural intelligence (CQ) as a micro-level construct describing intercultural competence has garnered growing attention in academic literature recently, resulting in an increase in research. This paper reports on the empirical research which, using as a survey instrument the Cultural Intelligence Scale (CQS) developed by Earley and Ang (2003), examined intercultural competencies of Polish EFL students at the tertiary education, measured by the level of CQ. In addition, the investigation aimed to analyze whether individual difference variables such as gender, educational level, linguistic proficiency, multilingualism, motivation to study English, and study abroad experience are significant predictors of students’ level of CQ. The results show that the respondents’ intercultural competence has been developed only to a small degree. Further, CQ is positively related to gender, educational level, foreign language proficiency, the number of foreign languages known, motivation to study English, and study abroad experience. Some practical applications of the study findings for the Polish tertiary education have been presented.